Cassava (Manihot esculenta) fermentation methods affected fufu yield, while drying and cold storage extended the shelf-life and consumer acceptability - Sama, Valentine; Molua, Ernest L.; Nkongho, Raymond Ndip; Ngosong, Christopher (Frontiers in Food Science and Technology, 2025)
Cassava (Manihot esculenta) fermentation methods can reduce the eventual fufu yield, while storage affects shelf-life and consumer acceptability. This study investigated effects of five cassava fermentation methods on fufu yield, and five storage methods on microbial load, sensory qualities and consumer acceptability of fufu. Fresh cassava roots were peeled, weighed and subjected to different fermentation methods for 5 days (e.g., tap water changed daily or every 2 days, tap water without change, borehole water without change, and tap water + bitterleaf (Vernonia amygdalina). The pH, temperature, total dissolved solids and turbidity of cassava fermentation effluent were measured daily for 5 days. Cassava fufu was stored at 0°C, 4°C, dried, in air-tight buckets and low-density polythene (LDPE) bags, and total titratable acid, pH, bacterial and fungal loads and consumer acceptability were evaluated weekly. A nine-point hedonic scale was used to assess consumer acceptability of fufu based on colour, dark spots, caking and odour. The highest fufu yield occurred in fermentation with tap water + bitterleaf (84%) and borehole water (82%) compared to when water was changed after 2 days (42%) and daily (38%). For storage at 4°C, 0°C, oven-dried, LDPE bags, and air-tight buckets in LDPE bags, respectively, bacterial load increased from 4 × 106 CFUs/mL at the start to 73, 32, 29, 145 and 85 × 106 CFUs/mL at week 4, while fungal load increased from 6 × 106 CFUs/mL at the start to 66, 32, 26, 96 and 89 × 106 CFUs/mL at week 4. Storage at 0°C and drying exhibited high consumer acceptability of cassava fufu compared to LDPE and air-tight buckets.